Heart Rate Variability in Children with Tricyclic Antidepressant Intoxication. (5th March 2013) - Dinleyici, Ener Cagri; Kilic, Zubeyir; Sahin, Sabiha; Tutuncu-Toker, Rabia; Eren, Makbule; Yargic, Zeynel Abidin; Kosger, Pelin; Ucar, Birsen
Abstract : The aim of this study was to evaluate HRV in children requiring intensive care unit stays due to TCA poisoning between March 2009 and July 2010. In the time-domain nonspectral evaluation, the SDNN (P < 0.001 ), SDNNi (P < 0.05 ), RMSDD (P < 0.01 ), and pNN50 (P < 0.01 ) were found to be significantly lower in the TCA intoxication group. The spectral analysis of the data recorded during the first 5 minutes after intensive care unit admission showed that the values of the nLF (P < 0.05 ) and the LF/HF ratio (P = 0.001 ) were significantly higher in the TCA intoxication group, while the nHF (P = 0.001 ) values were significantly lower. The frequency-domain spectral analysis of the data recorded during the last 5 minutes showed a lower nHF (P = 0.001 ) in the TCA intoxication group than in the controls, and the LF/HF ratio was significantly higher (P < 0.05 ) in the intoxication group. The LF/HF ratio was higher in the seven children with seizures (P < 0.001 ). These findings provided us with a starting point for the value of HRV analysis in determining the risk of arrhythmia and convulsion in TCA poisoning patients. HRV can be used as a noninvasive testing method in determining the treatment and prognosis of TCA poisoning patients.